2017
DOI: 10.4236/njgc.2017.73006
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Rare-Earth Ions in Sodium Aluminoborate Glasses Using <sup>23</sup>Na and <sup>27</sup>Al Magic Angle Spinning Nuclear Magnetic Resonance

Abstract: We conducted structural analysis of xNa 2 especially when the amount of these ions in the glasses increased. In addition to the above, the coordination number of Na + ions increased with an increase in the number of rare earth ions, confirmed by comparing results with NMR spectra of crystalline Na 2 Al 2 B 2 O 7 . The latter possibly occurred due to the oxygen concentration on Al [5] and Al [6] . Finally, it was confirmed that the formation of [5] Al and [6] Al decreases molar volume in oxide glasses, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The modifiers with a higher positive charge and thus a higher FS are more prone to attract the O atoms from the surroundings and thus create a more efficient packing of the structure. This has also been found in previous studies, in which it was also suggested that the higher coordination states of Al improve the packing efficiency . Increasing the modifier field strength also increases the glass-transition temperature ( T g ) (Figure b).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The modifiers with a higher positive charge and thus a higher FS are more prone to attract the O atoms from the surroundings and thus create a more efficient packing of the structure. This has also been found in previous studies, in which it was also suggested that the higher coordination states of Al improve the packing efficiency . Increasing the modifier field strength also increases the glass-transition temperature ( T g ) (Figure b).…”
Section: Resultssupporting
confidence: 87%
“…This has also been found in previous studies, in which it was also suggested that the higher coordination states of Al improve the packing efficiency. 36 Increasing the modifier field strength also increases the glass-transition temperature (T g ) (Figure 3b). The structural studies presented above reveal that the amounts of B IV and especially Al IV decrease with FS, implying less atomic constraints and thus smaller network connectivity.…”
Section: Methodsmentioning
confidence: 95%